Fuzzy Tsukamoto Method in Service Satisfaction Assessment at the Village Office Tanjung Aur 1 - Pransiska, Yance; Yulianti, Liza; Jumadi, Juju (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
IKM analysis must always be carried out periodically so that it can be seen that public satisfaction with the services provided, especially at the Tanjung Aur 1 Village Office. But in reality, so far the Tanjung Aur 1 Village Office has not had a benchmark that is used as a forum for knowing public satisfaction with these services.The application of the Fuzzy Tsukamoto Method in assessing service satisfaction at the Tanjung Aur 1 Village Office can assist in managing the results of the Community Satisfaction assessment of Services at the Tanjung Aur 1 Village Office, and can provide information on the results of measuring the level of community satisfaction with services at the Tanjung Aur 1 Village Office as an evaluation material to improve service quality. The application of the Fuzzy Tsukamoto Method in assessing service satisfaction at the Tanjung Aur 1 Village Office is built web-based using the PHP programming language and MySQL database which can be accessed online via the link https://kepuasandesatanjungaur1.site/, where there are 2 interface access rights in the application, namely Administrators and Villagers of Tanjung Aur 1. Based on the 2024 service satisfaction assessment data with 9 respondents who have been inputted into the web-based application, the results of the service satisfaction assessment that have been analysed through the Fuzzy Tsukamoto Method are Very Satisfied 44.44%, Satisfied 22.22%, Quite Satisfied 33.33%, Dissatisfied 0% and Very Dissatisfied 0%. Based on the results of the demo programme that has been carried out, 9 respondents have successfully provided service satisfaction assessments on the application online and also the operator can see the output of the satisfaction assessment results which will be given to the Village Head for evaluation.